Beyond Two-States: Alternative Visions of Self-Determination for the People of Palestine - Hodgkins, Allison (Tufts Archival Research Center, 2005)
Volume 28, Issue 2. Summer Allison Beth Hodgkins argues that the two-state solution to the Israeli-Palestinian conflict rests on mistaken notions of law, history, and practical reality, and urges the parties to consider the merits of collective self-determination.